ACUTE POISONING WITH BENZODIAZEPINES AND OTHER HYPNOTICS: ETIOLOGIC CAUSE, SEX/AGE DISTRIBUTION AND CLINICAL OUTCOME - Petko Marinov; Snezha Zlateva; Georgi Bonchev; Dobri Ivanov; Kaloyan Georgiev; Yulichka Sabeva; Marieta Yovcheva (Peytchinski Publishing, 2016)
Purpose: Poisoning with drugs occupies a leading position among the causes of acute intoxications. Etiological distribution of medicated poisoning in different countries, even if they are adjacent, is different. In the most studies it was reported that the highest incidence of poisoning is with benzodiazepines or other psychoactive drugs. A retrospective analysis of acute poisoning with benzodiazepines and other hypnotic drugs in the Varna region for 25 years period - from 1991 to 2015 was carried out. Material and Methods: The number of patients who received hospital treatment after poisoning with benzodiazepines is 1741, and those with other hypnotics is 293, representing respectively 26.37% and 4.44% of all drug intoxications. Results: The share of poisoning with benzodiazepines and hypnotics compared to all acute intoxications is 11.66%. They are more common in women - 1566 (77%). Men are 468 (23%), the ratio of men to women was 3.34:1. The largest number of intoxications is in the age group up to 24 years - 1123 (55.2%), and only 4.1% of patients over 60 years. Intentional suicide attempts are 1896 (93.2%). Death is registered in 8 (0.4%) patients.